Role of External Field in Polymerization: Mechanism and Kinetics - Zhou, Yin-Ning; Li, Jin-Jin; Wu, Yi-Yang; Luo, Zheng-Hong (Chemical reviews, 2020)
The past decades have witnessed an increasing interest in developing advanced polymerization techniques subjected to external fields. Various physical modulations, such as temperature, light, electricity, magnetic field, ultrasound, and microwave irradiation, are noninvasive means, having superb but distinct abilities to regulate polymerizations in terms of process intensification and spatial and temporal controls. Gas as an emerging regulator plays a distinctive role in controlling polymerization and resembles a physical regulator in some cases. This review provides a systematic overview of seven types of external-field-regulated polymerizations, ranging from chain-growth to step-growth polymerization. A detailed account of the relevant mechanism and kinetics is provided to better understand the role of each external field in polymerization. In addition, given the crucial role of modeling and simulation in mechanisms and kinetics investigation, an overview of model construction and typical numerical methods used in this field as well as highlights of the interaction between experiment and simulation toward kinetics in the existing systems are given. At the end, limitations and future perspectives for this field are critically discussed. This state-of-the-art research progress not only provides the fundamental principles underlying external-field-regulated polymerizations but also stimulates new development of advanced polymerization methods.